THE RELATIONSHIP BETWEEN STANDARDIZATION AND E-DRAWINGS IN LEARNING PROCESS - MONKOVA, Katarina; MONKA, Peter (Trends in education, 2009)
The article deals with relationship between standardization and e-drawings. It shows on the need of theoretical base acquisition for design documentation creating in learning process and its application in the selected CAD tool. Article describes the necessity and the possibilities of drawing documentation set up and the meaning of basic terms in the scope of CAD/CAM system Pro/Engineer.
Keywords: standardization; drawing documentation; CAD system; configuration file; setup parameters.